The Cenomanian-Turonian boundary and Oceanic Anoxic Event 2 in the eastern Neotethys: A multi-proxy study of the I•nis, dere area of southeast Türkiye - Mulayim, Oguz; Koroglu, Fatih; Alkac, Onur (Elsevier, 2025)
The Southeastern Anatolian Basin contains the region's most significant hydrocarbon source rocks within Cretaceous (Cenomanian-Turonian) carbonate successions, with the largest accumulations occuring in the I(center dot)nis, dere region of Ad & imath;yaman, southeastern T & uuml;rkiye. In this paper, we compile comprehensive biostratigraphic data for these neritic and hemipelagic facies to improve chronostratigraphic calibration of standard biozones for fossil groups. Stratigraphic analyses including major, trace, and rare earth elements, total organic carbon (TOC), stable isotopes (S13C and S18O), and 87Sr/86Sr isotopes were also performed. Our findings highlight the development of organic-rich limestones (TOC 0.85-2.92 wt%) in the lower Turonian part of the succession, and the concentration of redox-sensitive elements (U, V, Co, As, and Cr) in these beds suggest that anoxia created optimal conditions for organic carbon preservation. Stable isotope data allows us to correlate this interval with Ocean Anoxic Event 2 (OAE2), which coincided with regional platform drowning, and further enables detailed stratigraphic comparison with palaeoenvironmental records from other regions of the Tethys Ocean.
Keywords: Chemostratigraphy; Cenomanian-Turonian boundary; Geochemistry; Neotethys; Ocean Anoxic Event 2